KONSEP SIGNIFIKAN MANAJEMEN RESIKO OPERASIONAL PERBANKAN SYARIAH - Nuriant, Ulfia; Fitria, Anis (Izdihar: Jurnal Ekonomi Syariah, 2022)
The purpose of this article is to find out what operational risk management is and its causes. This article uses literature study research or literature study. Data collection techniques by collecting references consisting of several previous studies by reviewing several journals to review operational risk management. In Islamic banking, there are several risks that cannot be avoided because of its function as a financial intermediary institution. One of the risks faced by banks is operational risk which becomes an obstacle to the goals desired by the bank. The results of this study are operational risk caused by four (4) factors, the first is due to an internal process error, the second is human failure, the third is system failure and the fourth is external events. Therefore, banks must carry out risk management to minimize the risks that will occur so as not to cause unwanted losses.